THE INFLUENCE OF USING ULTRASOUNDS FOR IMPROVING THE SEALING ABILITY OF THE PERMANENT ROOT CANAL FILLING - Cristian Levente Giuroiu; Horia Aldea; Raluca Dragomir; Galina Pancu; Cătălina Dănilă; Silvia Teslaru; Sorin Andrian (Romanian Society of Oral Rehabilitation, 2015)
This paper aims to evaluate ,,in vitro'' the tightness of root fillings in monoradicular teeth using distinct techniques: monocone classic technique, cold lateral condensation technique and warm vertical condensation ultrasound associated technique, underlining some issues of particular interest regarding clinical outcomes over time for endodontic treatment. The study group consists of 45 permanent, monoradicular maxillary and mandibular teeth. The study results showed a higher degree of dye infiltration in the teeth root, filled with monocone classic technique compared to cold lateral condensation and hot vertical condensation ultrasound associated methods; slightly higher dye infiltration in teeth filled by cold lateral condensation technique compared to the teeth group with hot vertical condensation ultrasound associated technique; the control group showed overall richest dye penetration in root canals and dentinal tubules. Warm root canal filling with fluid gutta-percha makes a more qualitative 3D sealing, especially in the medium and coronal thirds compared to other techniques used.